Long‐term follow‐up of the Medical Research Council CLASICC trial of conventional versus laparoscopically assisted resection in colorectal cancer. Issue 1 (6th November 2012) - Green, B. L.; Marshall, H. C.; Collinson, F.; Quirke, P.; Guillou, P.; Jayne, D. G.; Brown, J. M.
Abstract Background: Laparoscopic resection is used widely in the management of colorectal cancer; however, the data on long‐term outcomes, particularly those related to rectal cancer, are limited. The results of long‐term follow‐up of the UK Medical Research Council trial of laparoscopically assisted versus open surgery for colorectal cancer are presented. Methods: A total of 794 patients from 27 UK centres were randomized to laparoscopic or open surgery in a 2:1 ratio between 1996 and 2002. Long‐term follow‐up data were analysed to determine differences in survival outcomes and recurrences for intention‐to‐treat and actual treatment groups. Results: Median follow‐up of all patients was 62·9 (interquartile range 22·9 − 92·8) months. There were no statistically significant differences between open and laparoscopic groups in overall survival (78·3 (95 per cent confidence interval (c.i.) 65·8 to 106·6) versus 82·7 (69·1 to 94·8) months respectively; P = 0·780) and disease‐free survival (DFS) (89·5 (67·1 to 121·7) versus 77·0 (63·3 to 94·0) months; P = 0·589). In colonic cancer intraoperative conversions to open surgery were associated with worse overall survival (hazard ratio (HR) 2·28, 95 per cent c.i. 1·47 to 3·53; P < 0·001) and DFS (HR 2·20, 1·31 to 3·67; P = 0·007). In terms of recurrence, no significant differences were observed by randomized procedure. However, at 10 years, right colonic cancers showed an increased propensity for local recurrence compared with left colonic cancers: 14·7 versus 5·2 per cent (difference 9·5 (95 per cent c.i. 2·3 to 16·6) per cent; P = 0·019). Conclusion: Long‐term results continue to support the use of laparoscopic surgery for both colonic and rectal cancer. Copyright © 2012 British Journal of Surgery Society Ltd. Published by John Wiley & Sons, Ltd.